Enhancing Geometry Achievement in Pre-Service Mathematics Teachers: The Impact of a Scaffolded Flipped Classroom Using a Learning Management System - Awi, Awi; Naufal, Muhammad Ammar; Sutamrin, Sutamrin; Huda, Miftachul (Journal of Ecohumanism, 2024)
This study investigates the effectiveness of a flipped classroom approach integrated with scaffolding through a Learning Management System (LMS) in enhancing the geometry achievement of pre-service mathematics teachers. The study utilized an experimental post-test-only control group design involving 63 randomly selected pre-service mathematics teachers. The experimental group received instruction through a flipped classroom model supplemented with scaffolding and LMS support, while the control group experienced traditional teaching methods enhanced by scaffolding and LMS. Quantitative data were collected via a geometry essay test and analyzed using descriptive and inferential statistics, including t-tests. The results revealed that the experimental group significantly outperformed the control group in geometry achievement. Additionally, qualitative data from thematic analysis of semi-structured interviews indicated that the flipped classroom approach fostered improved comprehension, peer interaction, and active discussion, despite challenges such as varying levels of motivation and scheduling conflicts. The scaffolding provided was found to be an effective strategy in clarifying complex topics and enhancing student success. This study underscores the potential of integrating a flipped classroom with scaffolding and LMS to improve geometry achievement and overall instructional quality.